Aktivitas Antioksidan Senyawa Asam 5(E)-Eikosenoat dari Batang Tanaman Polygonum pulchrum Bl - Malaka, Muhammad Hajrul; Yodha, Agung Wibawa Mahatva; Azhar, Muhammad; Hamsidi, Rini; Sahidin, Sahidin (Fakultas Farmasi Universitas Halu Oleo, 2015)
Isolation and identification of secondary metabolite stem bark of Polygonum pulchrum and its antioxidant activity were done. Extraction was performed by maceration using methanol solvent. The separation and purification obtained by using vacuum liquid chromatography (VLC), radial chromatography (RC) and monitored by thin layer chromatography (TLC). Identification of isolated compounds determined by spectroscopy method i.e. FT-IR, 1D-NMR (1H, 13C-NMR and DEPT) and 2-D NMR (HMQC and HMBC). White solid compound was isolated and characterized as 5(E)-eicosenoic acid. Antioxidant was analyzed towards DPPH (1,1-diphenyl-picrilhydrazil). The compound showed that has antioxidant potency with IC50 value at 348.10 ÂµM.Keywords: Polygonum pulchrum, 5(E)-eicosenoic acid, antimicrobial, antioxidantÂ